Positive allosteric modulator selective for adult muscle nicotinic acetylcholine receptor - Richard G. Webster; Setareh Alabaf; Anna Li; Rene Beerli; Sandra Siehler; Pierre-Eloi Imbert; Leonard Lee; Judith Cossins; Magdalena Koziczak-Holbro; Ludivine Flotte; Laurent Gaudet; Nicole Gerwin; et al. (Proceedings of the National Academy of Sciences, 2026)
The muscle nicotinic acetylcholine receptor (AChR) is the key mediator of neuromuscular signal transmission and is essential for all voluntary movement in our body. In this study, we present DC-98-LC74, a positive allosteric modulator (PAM) for the adult skeletal muscle-type AChR. Through using Ca 2+ fluorometric imaging plate reader (FLIPR) assays, we demonstrate that it is selective for the adult skeletal muscle AChR over neuronal subtypes. Neurophysiological recordings from ex vivo mouse diaphragm preparations revealed that DC-98-LC74 elongates the endplate currents of wildtype (WT) adult but not fetal channel containing diaphragms. Single channel studies on chimeric channels of the adult and fetal receptor, and in saturating concentrations of choline, suggest that the PAM does not bind at either orthosteric site, but works by increasing the unliganded open probability via a mechanism that involves the ε M2-M3 loop. We also show that DC-98-LC74 increases the burst duration of multiple fast channel mutant AChR to WT levels, suggesting that positive allosteric modulation could be a therapeutic strategy for this difficult to treat subtype of congenital myasthenia. Promising preliminary data on aged sarcopenic mice also demonstrate that positive allosteric modulation of the muscle type AChR has potential benefits not only in myasthenia but also other neuromuscular disorders involving the neuromuscular junction.